2015
DOI: 10.2174/1570162x1303150506181945
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Discontinuation in Adult HIV-Infected Patients on First-Line Antiretroviral Therapy in Nigeria

Abstract: Long-term treatment discontinuation rate in this study was comparable to estimates in resource-rich countries. Younger patients, as well as patients with lower educational levels and those with poor adherence had significant hazards for treatment discontinuation and should be the target of interventions to reduce treatment discontinuation and improve retention, especially within the first year of ART.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 0 publications
1
5
1
Order By: Relevance
“…When compared to findings elsewhere in Ethiopia, discontinuation rate in the current study was higher than findings from the Tigray’s study [14] and lower than findings from the Amhara’s study [15]. In addition, this rate was lower than findings from studies conducted in Guinea-Bissau (51.1%)[39], Nigeria (28%)[40], and a multi-clinic study from Republic of Congo, Cameron and Burundi (83%)[41]. The dissimilarity in measurement[42], access to HIV care services[43], and innovation, adoption and implementation of cost-effective retention strategies could be the possible reasons of differences[44, 45].…”
Section: Discussioncontrasting
confidence: 84%
“…When compared to findings elsewhere in Ethiopia, discontinuation rate in the current study was higher than findings from the Tigray’s study [14] and lower than findings from the Amhara’s study [15]. In addition, this rate was lower than findings from studies conducted in Guinea-Bissau (51.1%)[39], Nigeria (28%)[40], and a multi-clinic study from Republic of Congo, Cameron and Burundi (83%)[41]. The dissimilarity in measurement[42], access to HIV care services[43], and innovation, adoption and implementation of cost-effective retention strategies could be the possible reasons of differences[44, 45].…”
Section: Discussioncontrasting
confidence: 84%
“…The regimen change rate found in the current study is higher than findings elsewhere in Ethiopia [ 12 , 26 ]. It is also higher when compared to other cohort studies in Uganda (39.21%) [ 27 ] and Nigeria (28%) [ 28 ]. However, cohort studies from resource-rich countries like UK, Italy, and Brazil showed higher incidence rates of regimen changes (28.3–41.5 per 100 PY) [ 17 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 54%
“…Patients with suboptimal adherence were at an increased risk of being lost to follow up when compared with those with good adherence. This was supported by studies conducted in Nigeria [16] and Vietnam [34]. The possible reason could be patients with sub-optimal adherence may have socio-demographic and clinical problems that affect their adherence initially which further affect retention in care [35].…”
Section: Discussionmentioning
confidence: 85%
“…Lost to follow up from HIV care was positively associated with young age [9, 13, 14], male sex [14, 15] single marital status [13, 16], illiteracy [13, 16], long travel time to the clinic [14, 17], bedridden functional status [18, 19], presence of opportunistic infections (OIs) and opportunistic infection prophylaxis [20, 21] low CD4 count [9, 18, 22] less advanced WHO clinical stage [21].…”
Section: Introductionmentioning
confidence: 99%